A method for preparing polyolefin / graphene nanocomposite material by utilizing mechanical shear force
Polyolefin/graphene nanocomposite materials are prepared by mechanical shear force shear mixing method, which solves the problems of complex preparation process and uneven dispersion of graphene nanofillers in the existing technology, and achieves high performance and environmentally friendly production of composite materials.
Patent Information
- Application Number
- CN202110464675.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-04-28
AI Technical Summary
The existing preparation methods for polyolefin/graphene nanocomposites have problems such as complex preparation process, high equipment requirements, environmental pollution and uneven dispersion of graphene nanofillers.
Preparing polyolefin/graphene nanocomposite materials by shear mixing method using mechanical shear force, including shear mixing graphene nanosheets, polyolefin powder and N-methylpyrrolidone under the action of mechanical shear force, and The solvent is removed by drying to obtain a uniformly dispersed composite material.
The uniform dispersion of graphene nanosheets in the polyolefin matrix is achieved, which enhances the antistatic properties, impact resistance, rigidity and heat resistance of the composite material. The production process is environmentally friendly and efficient, and is suitable for large-scale industrial preparation.
Smart Images

Figure CN115246964B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer advanced material preparation, and more specifically, to a method for preparing a polyolefin / graphene nanocomposite material by utilizing mechanical shearing force. Background Art
[0002] The preparation of polyolefin / graphene nanocomposites is mainly concentrated on solution mixing, in-situ polymerization and melt mixing. The former two have problems such as complex preparation process and stringent equipment requirements. The pressure of environmental protection and manufacturing cost brought by the large-scale use of organic solvents (toluene and xylene) further limits their large-scale application. The traditional melt mixing preparation method cannot achieve uniform dispersion of graphene nanofillers in the polyolefin matrix.
[0003] In order to achieve uniform dispersion of graphene nanofillers in a polyolefin matrix and avoid agglomeration, existing public technologies mostly focus on chemical treatment, that is, using the functional groups on the surface of graphene oxide, a derivative of graphene, for functional modification, such as grafting isocyanate, silane coupling agent and polymer chain, etc., which can effectively promote the dispersion of graphene nanofillers in a polyolefin matrix. However, the chemical modification process is complicated and has high requirements for production equipment, which is not conducive to industrial large-scale production. In addition, during the oxidation-reduction process, the conductivity and mechanical properties of graphene will be reduced to varying degrees.
[0004] Therefore, it is necessary to provide a new method for preparing a polyolefin / graphene nanocomposite material to solve the above problems. Summary of the invention
[0005] The first object of the present invention is to provide a method for preparing a polyolefin / graphene nanocomposite material by utilizing mechanical shear force, wherein the method effectively enhances the antistatic property, impact resistance, rigidity and heat resistance of the polyolefin / graphene nanocomposite material.
[0006] The second object of the present invention is to provide a polyolefin / graphene nanocomposite material obtained by the above method.
[0007] To achieve the above object, the present invention first provides a method for preparing a polyolefin / graphene nanocomposite material by using mechanical shear force, comprising the following steps:
[0008] The graphene nanosheets, polyolefin powder and N-methylpyrrolidone are shear-mixed under the action of mechanical shear force to obtain a shear-mixed product;
[0009] The product after the shear mixing treatment is dried to remove the N-methylpyrrolidone, thereby obtaining a polyolefin / graphene nanocomposite material.
[0010] Further, the shear mixing is performed at a temperature of 90°C-120°C and a torque of 15-20N·m for 0.5-3h; preferably, the shear mixing is performed at a temperature of 90°C and a torque of 15N·m for 1h. The present invention shows that the surface resistivity and volume resistivity of the polypropylene / graphene nanocomposite material show a downward trend with the extension of the shear mixing time during the preparation of the polypropylene / graphene nanocomposite material, indicating that increasing the shear time can make the sample mix more uniformly. It is also found that when the shear time is greater than 1h, the surface resistivity and volume resistivity of the composite material have a smaller range of variation, indicating that the graphene nanosheets can be uniformly dispersed in the polypropylene matrix after a treatment of 1h. Therefore, the optimal shear mixing condition of the present invention is shear mixing at a temperature of 90°C and a torque of 15N·m for 1h.
[0011] Furthermore, the polyolefin powder is a thermoplastic polymer material such as polypropylene powder, polyethylene powder, polystyrene powder and / or polyvinyl chloride powder. In the specific embodiment of the present invention, the dispersion of graphene nanosheets in the polypropylene matrix is achieved only by mechanical shear force. Since no chemical reaction occurs during the preparation process, the matrix can be replaced by other thermoplastic polymers such as polyethylene, polystyrene and polyvinyl chloride by analogy.
[0012] Furthermore, the graphene nanosheets account for 0.5%-3.5% of the total mass of the graphene nanosheets and the polyolefin powder.
[0013] Furthermore, the N-methylpyrrolidone accounts for 5-15% of the total mass of the graphene nanosheets and the polyolefin powder; preferably 10%.
[0014] Furthermore, the drying is performed at 40-70° C. for 8-16 hours; preferably, the drying is performed at 50° C. for 12 hours.
[0015] In the process of preparing the polyolefin / graphene nanocomposite material, the mechanical shear force promotes the dispersion of the graphene nanosheets in the polyolefin matrix and further prevents the reagglomeration of the filler graphene in the dispersion process. A small amount of solvent N-methylpyrrolidone plays the role of a lubricant, so that the graphene nanosheets and the polyolefin matrix are subjected to a milder and more uniform shear force, which promotes the strengthening of the interface bonding force between the graphene and the polymer matrix, and improves the electrical conductivity, mechanical properties (i.e., impact strength and rigidity) and thermal stability of the polyolefin / graphene nanocomposite material.
[0016] The polyolefin / graphene nanocomposite material prepared by the above preparation method is also within the protection scope of the present invention.
[0017] Furthermore, the general formula of the polyolefin / graphene nanocomposite material is PP / Gx, where x represents the mass percentage of graphene nanosheets in the polyolefin / graphene nanocomposite material, and x is 0.5%-3.5%.
[0018] The microstructure of the polypropylene / graphene nanocomposite obtained by the present invention shows that the graphene nanosheets have good dispersibility in the polypropylene / graphene nanocomposite system. On the one hand, the dispersibility of the graphene nanosheets significantly improves the antistatic properties and mechanical properties (including impact strength and rigidity, and the rigidity is characterized by yield strength and Young's modulus) of the polypropylene / graphene nanocomposite. When the addition amount of the graphene nanosheets is 1wt%, the surface resistivity of the polypropylene / graphene nanocomposite is 2.4×10 7 Ω / sq, which can meet the requirements of actual commercial antistatic materials less than 3×10 8 Ω / sq standard, a lower conductive percolation threshold is obtained, the impact strength is increased by 120.8% relative to pure polypropylene, and the yield strength and Young's modulus are increased by 19.2% and 27.7%, respectively. On the other hand, the addition of a small amount of graphene nanosheets can greatly improve the thermal stability of the polypropylene / graphene nanocomposite material. When the addition amount of graphene nanosheets is 1wt%, the HDT of the polypropylene / graphene nanocomposite material is increased by 11.7°C. Therefore, the present invention has positive significance for promoting the high-performance application of polyolefin / graphene nanocomposites.
[0019] The beneficial effects of the present invention are as follows:
[0020] The invention prepares a polypropylene / graphene nanocomposite material by a shear mixing method using a mechanical shear force, promotes uniform dispersion of graphene nanosheets in a polyolefin matrix, maintains the original conjugated structure of the graphene nanosheets, enables the graphene nanosheets to induce polypropylene to form a beta crystal with higher impact strength without changing the crystallinity, can more effectively improve the electrical conductivity, mechanical properties (impact strength and rigidity) and thermal stability of the composite material, obtains a lower electrical conductivity percolation threshold, and has high efficiency and environmental protection in production, reduces the pressure caused by post-processing and cost, and is conducive to large-scale industrial preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.
[0022] Figure 1The macroscopic morphology and microscopic morphology of pure polypropylene (PP), pure graphene nanosheets (GNP) and polypropylene / graphene nanocomposites prepared in the examples are shown; wherein a) and b) are microscopic morphology of pure PP and pure GNP, respectively; c) is a macroscopic morphology of the polypropylene / graphene nanocomposite PP / G1.0% obtained in Example 2; d), e) and f) are microscopic morphology of the polypropylene / graphene nanocomposites PP / G0.5%, PP / G1.0% and PP / G3.5% obtained in Examples 1, 2 and 5, respectively.
[0023] Figure 2 a) and b) are the surface resistivity and volume resistivity of the polypropylene / graphene nanocomposites prepared in Examples 1-5, respectively.
[0024] Figure 3 In which a) and b) are the surface resistivity and volume resistivity of the polypropylene / graphene nanocomposites prepared in Examples 7-11, respectively.
[0025] Figure 4 The impact strength of the polypropylene / graphene nanocomposite materials prepared in Examples 1-5.
[0026] Figure 5 The yield strength and Young's modulus of the polypropylene / graphene nanocomposite materials prepared in Examples 1-5.
[0027] Figure 6 is the thermal deformation temperature of the polypropylene / graphene nanocomposite material prepared in Examples 1-5. DETAILED DESCRIPTION
[0028] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0029] Example 1 A polypropylene / graphene nanocomposite material
[0030] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0031] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added into a torque rheometer (wherein, the addition amount of GNP was 0.5% of the total mass of GNP and PP, and the addition amount of NMP was 10% of the total mass of GNP and PP), and shear mixed for 1 hour at a temperature of 90° C. and a torque of 15 N·m, so that the graphene nanosheets were uniformly dispersed under the action of mechanical shear force, and the product after shear mixing was dried at 50° C. for 12 hours in a vacuum drying oven to remove NMP, thereby obtaining a polypropylene / graphene nanocomposite material, which has the general formula of PP / Gx, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the addition amount of GNP. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G0.5%.
[0032] Example 2 A polypropylene / graphene nanocomposite material
[0033] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0034] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added into a torque rheometer (wherein, the addition amount of GNP was 1% of the total mass of GNP and PP, and the addition amount of NMP was 10% of the total mass of GNP and PP), and shear mixed for 1 hour at a temperature of 90° C. and a torque of 15 N·m, so that the graphene nanosheets were uniformly dispersed under the action of mechanical shear force, and the product after shear mixing was dried at 50° C. for 12 hours in a vacuum drying oven to remove NMP, thereby obtaining a polypropylene / graphene nanocomposite material, which has the general formula of PP / Gx, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the addition amount of GNP. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G1.0%.
[0035] Example 3 A polypropylene / graphene nanocomposite material
[0036] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0037] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added into a torque rheometer (wherein, the addition amount of GNP was 1.5% of the total mass of GNP and PP, and the addition amount of NMP was 10% of the total mass of GNP and PP), and shear mixed for 1 hour at a temperature of 90° C. and a torque of 15 N·m, so that the graphene nanosheets were uniformly dispersed under the action of mechanical shear force, and the product after shear mixing was dried at 50° C. for 12 hours in a vacuum drying oven to remove NMP, thereby obtaining a polypropylene / graphene nanocomposite material, which has the general formula of PP / Gx, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the addition amount of GNP. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G1.5%.
[0038] Example 4 A polypropylene / graphene nanocomposite material
[0039] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0040] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added into a torque rheometer (wherein, the amount of GNP added was 2.5% of the total mass of GNP and PP, and the amount of NMP added was 10% of the total mass of GNP and PP), and shear mixed for 1 hour at a temperature of 90° C. and a torque of 15 N·m, so that the graphene nanosheets were uniformly dispersed under the action of mechanical shear force, and the product after shear mixing was dried at 50° C. for 12 hours in a vacuum drying oven to remove NMP, thereby obtaining a polypropylene / graphene nanocomposite material, which has the general formula of PP / Gx, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the amount of GNP added. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G2.5%.
[0041] Example 5 A polypropylene / graphene nanocomposite material
[0042] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0043] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added into a torque rheometer (wherein, the addition amount of GNP was 3.5% of the total mass of GNP and PP, and the addition amount of NMP was 10% of the total mass of GNP and PP), and shear mixed for 1 hour at a temperature of 90° C. and a torque of 15 N·m, so that the graphene nanosheets were uniformly dispersed under the action of mechanical shear force, and the product after shear mixing was dried at 50° C. for 12 hours in a vacuum drying oven to remove NMP, thereby obtaining a polypropylene / graphene nanocomposite material, which has the general formula of PP / Gx, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the addition amount of GNP. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G3.5%.
[0044] Example 6 A polypropylene / graphene nanocomposite material
[0045] A method for preparing a polypropylene / graphene nanocomposite material comprises the following steps:
[0046] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added into a torque rheometer (wherein the amount of GNP added was 2.5% of the total mass of GNP and PP, and the amount of NMP added was 10% of the total mass of GNP and PP), without shear mixing treatment, to obtain a polypropylene / graphene nanocomposite material, the general formula of which is PP / Gx-&, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e. the amount of GNP added, and & represents the shear mixing time. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G2.5%-0.
[0047] Example 7 A polypropylene / graphene nanocomposite material
[0048] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0049] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added to a torque rheometer (wherein the amount of GNP added was 2.5% of the total mass of GNP and PP, and the amount of NMP added was 10% of the total mass of GNP and PP), and shear mixed for 10 min at a temperature of 90°C and a torque of 15 N·m. The product after shear mixing was dried in a vacuum drying oven at 50°C for 12 h, and NMP was removed to obtain a polypropylene / graphene nanocomposite material with the general formula of PP / Gx-&, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the amount of GNP added, and & represents the shear mixing time. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G2.5%-10min.
[0050] Example 8 A polypropylene / graphene nanocomposite material
[0051] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0052] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added into a torque rheometer (wherein, the amount of GNP added was 2.5% of the total mass of GNP and PP, and the amount of NMP added was 10% of the total mass of GNP and PP), and shear mixed for 30 min at a temperature of 90°C and a torque of 15 N·m. The product after shear mixing was dried in a vacuum drying oven at 50°C for 12 h, and NMP was removed to obtain a polypropylene / graphene nanocomposite material, the general formula of which is PP / Gx-&, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the amount of GNP added, and & represents the shear mixing time. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G2.5%-30min.
[0053] Example 9 A polypropylene / graphene nanocomposite material
[0054] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0055] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added to a torque rheometer (wherein the amount of GNP added was 2.5% of the total mass of GNP and PP, and the amount of NMP added was 10% of the total mass of GNP and PP), and shear mixed for 1 hour at a temperature of 90°C and a torque of 15 N·m. The product after shear mixing was dried in a vacuum drying oven at 50°C for 12 hours, and NMP was removed to obtain a polypropylene / graphene nanocomposite material with the general formula of PP / Gx-&, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the amount of GNP added, and & represents the time of shear mixing. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G2.5%-1h.
[0056] Example 10 A polypropylene / graphene nanocomposite material
[0057] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0058] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added to a torque rheometer (wherein the amount of GNP added was 2.5% of the total mass of GNP and PP, and the amount of NMP added was 10% of the total mass of GNP and PP), and shear mixed for 2 hours at a temperature of 90°C and a torque of 15N·m. The product after shear mixing was dried in a vacuum drying oven at 50°C for 12 hours, and NMP was removed to obtain a polypropylene / graphene nanocomposite material with the general formula of PP / Gx-&, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the amount of GNP added, and & represents the time of shear mixing. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G2.5%-2h.
[0059] Example 11 A polypropylene / graphene nanocomposite material
[0060] A method for preparing a polypropylene / graphene nanocomposite material by utilizing mechanical shear force comprises the following steps:
[0061] Graphene nanosheets (GNP), polypropylene (PP) powder and N-methylpyrrolidone (NMP) were added to a torque rheometer (wherein the amount of GNP added was 2.5% of the total mass of GNP and PP, and the amount of NMP added was 10% of the total mass of GNP and PP), and shear mixed for 3 hours at a temperature of 90°C and a torque of 15N·m. The product after shear mixing was dried in a vacuum drying oven at 50°C for 12 hours, and NMP was removed to obtain a polypropylene / graphene nanocomposite material with the general formula of PP / Gx-&, where x represents the mass percentage of GNP in the polypropylene / graphene nanocomposite material, i.e., the amount of GNP added, and & represents the time of shear mixing. Therefore, the polypropylene / graphene nanocomposite material obtained in this embodiment is PP / G2.5%-3h.
[0062] Test Example Performance Determination of Polypropylene / Graphene Nanocomposites Obtained from Examples 1-5 and 6-11
[0063] The macroscopic and microscopic morphologies of the polypropylene / graphene nanocomposites obtained in Examples 1-5, as well as pure PP (i.e., raw material PP) and pure GNP (i.e., raw material GNP) were observed using a Hitachi S-4800 scanning electron microscope. Figure 1 As shown in the figures, a) and b) respectively give the microscopic morphologies of pure PP and pure GNP, c) gives the macroscopic morphology of the polypropylene / graphene nanocomposite material PP / G1.0% obtained in Example 2, d), e) and f) are the microscopic morphologies of the polypropylene / graphene nanocomposite materials PP / G0.5%, PP / G1.0% and PP / G3.5% obtained in Examples 1, 2 and 5 respectively, showing that the polypropylene / graphene nanocomposite material obtained in the present invention achieves uniform dispersion of GNPs in the PP matrix both on a macroscopic and microscopic scale, and the two are tightly combined, indicating that the mechanical shear force provided by the shear mixing process in the preparation of the polypropylene / graphene nanocomposite material of the present invention effectively promotes the dispersion of GNPs and makes the combination between GNPs and PP closer.
[0064] The surface resistivity and volume resistivity of the polypropylene / graphene nanocomposites obtained in Examples 1-5 were measured using an ACL Model 800 high resistance meter at room temperature. The sample size was 100×100×2 mm. 3 , the results are as follows Figure 2 As shown in a) and b), with the increase of GNP addition, the surface resistivity and volume resistivity of polypropylene / graphene nanocomposites show a downward trend, indicating that filler GNP can improve the insulation of PP matrix. Among them, when the addition amount of GNP is 0.5wt%, the surface resistivity is 5.37×10 11 Ω / sq and volume resistivity is 7.35×10 11Ω·cm. When the amount of GNP added increased to 1.0%, the surface resistivity suddenly increased to 2.40×10 7 Ω / sq and volume resistivity is 6.37×10 5 Ω·cm (or the surface resistivity and volume resistivity of the composite material are 2.40×10 7 Ω / sq and 6.37×10 5 Ω·cm, there is an obvious mutation) indicating that the percolation threshold is 1.0wt%, and this addition amount can meet the surface resistivity of the antistatic material in practical applications less than 3×10 8 Ω / sq. The percolation threshold obtained by the preparation methods with better dispersion effect recognized by researchers, such as in-situ polymerization and solution mixing, is about 1.0wt%. The percolation threshold obtained by this method is comparable to the values obtained by the above two methods. In addition, this method avoids the problems of cost, post-processing and environmental pollution caused by the large-scale use of solvents, and has a relatively broad prospect for industrial application. At the same time, the surface resistivity and volume resistivity of the polypropylene / graphene nanocomposites obtained in Examples 6-11 were measured. The surface resistivity and volume resistivity of Example 6 were both greater than 10 12 , indicating that the polypropylene / graphene composite material obtained in this example has poor conductivity due to poor dispersibility. The surface resistivity and volume resistivity results of Examples 7-11 are as follows Figure 3 As shown in a) and b), the surface resistivity and volume resistivity of the polypropylene / graphene nanocomposite material show a downward trend as the shear mixing time increases, indicating that increasing the shear time can make the sample mix more uniformly. It is also found that when the shear time is greater than 1h, the surface resistivity and volume resistivity of the composite material change in a smaller range, indicating that the graphene nanosheets can be evenly dispersed in the polypropylene matrix after a treatment of 1h.
[0065] The impact resistance of the polypropylene / graphene nanocomposites prepared in Examples 1-5 was tested using an XJ-300A material impact testing machine. The results are as follows: Figure 4 As shown in Figure 2, the impact strength of polypropylene / graphene nanocomposites increases with the increase in the amount of GNPs added. When the amount of GNPs added is 1wt%, the impact strength reaches a maximum value of 10.6KJ / m 2 , compared with pure PP (4.8KJ / m 2 ), which shows that GNP has significant toughening ability. The tensile mechanical properties of the polypropylene / graphene nanocomposites prepared in Examples 1-5 were tested using an Instron 5966 universal mechanical testing machine. The results are as follows: Figure 5As shown, the yield strength and Young's modulus of the polypropylene / graphene nanocomposite material increase with the increase of the addition amount of GNP. When the addition amount of GNP is 0.5wt%, the yield strength and Young's modulus are 37.3MPa and 1184.3MPa, which can be increased by 13.7% and 25.3% respectively relative to pure PP (32.8MPa, 945.3MPa), which shows that adding a small amount of graphene nanosheets can effectively enhance the rigidity of the polypropylene / graphene nanocomposite material. When the addition amount of GNP is 3.5wt%, the Young's modulus and yield strength reach the maximum value, which is increased by 29.9% and 76.7% respectively relative to pure PP, which can significantly improve the rigidity of the polypropylene / graphene nanocomposite material. The above description shows that the preparation method of the present invention can significantly improve the mechanical properties of the polypropylene / graphene nanocomposite material.
[0066] Heat deformation temperature (HDT) is one of the commonly used indicators to measure the actual heat resistance of materials, representing the maximum temperature that a material can withstand under normal mechanical behavior. The heat deformation temperature of the polypropylene / graphene nanocomposites prepared in Examples 1-5 was measured using a HDV / V-3116 heat deformation Vicat softening point thermometer. The results are as follows: Figure 6 As shown, the HDT of the polypropylene / graphene nanocomposite increases with the increase of the amount of GNP added, which shows that compared with pure PP, the polypropylene / graphene nanocomposite can maintain its normal shape and rigidity at higher temperatures. When the amount of GNP added is as low as 0.5%, the HDT of the polypropylene / graphene nanocomposite is 95.9°C, which is 11.7°C higher than that of pure PP (84.2°C), indicating that when the amount of GNP added is small, the use temperature range of the polypropylene / graphene nanocomposite can be greatly expanded, which has certain practical value. When the amount of GNP added is 3.5wt%, the HDT can be increased by up to 31.1°C, which can significantly increase the maximum use temperature of the polypropylene / graphene nanocomposite.
[0067] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a polyolefin / graphene nanocomposite material using mechanical shear force, characterized in that: It consists of the following steps: Adding graphene nanosheets, polyolefin powder and N-methylpyrrolidone into a torque rheometer, performing shear mixing under the action of mechanical shear force, and obtaining a shear mixed product; The product after the shear mixing treatment is dried to remove the N-methylpyrrolidone, thereby obtaining a polyolefin / graphene nanocomposite material; The shear mixing is performed at a temperature of 90°C-120°C and a torque of 15-20 N·m for 0.5-3h; The N-methylpyrrolidone accounts for 5-15% of the total mass of the graphene nanosheets and the polyolefin powder; The graphene nanosheets account for 1% to 3.5% of the total mass of the graphene nanosheets and the polyolefin powder; The polyolefin powder is polypropylene powder.
2. The method according to claim 1, characterized in that The shear mixing is carried out at a temperature of 90° C. and a torque of 15 N·m for 1 hour.
3. The method according to claim 1, characterized in that The N-methylpyrrolidone accounts for 10% of the total mass of the graphene nanosheets and the polyolefin powder.
4. The method according to claim 1, characterized in that: The drying is performed at 40-70° C. for 8-16 hours.
5. The method according to claim 1, characterized in that The drying step is drying at 50° C. for 12 h.
6. A method for preparing a polyolefin / graphene nanocomposite material using mechanical shear force, characterized in that: It consists of the following steps: Adding graphene nanosheets, polypropylene powder and N-methylpyrrolidone into a torque rheometer; wherein the amount of graphene nanosheets added is 1%, 1.5%, 2.5% or 3.5% of the total mass of the graphene nanosheets and the polypropylene powder, and the amount of N-methylpyrrolidone added is 10% of the total mass of the graphene nanosheets and the polypropylene powder; The shear mixing was carried out at a temperature of 90° C. and a torque of 15 N·m for 1 h, and the product after the shear mixing treatment was dried in a vacuum drying oven at 50° C. for 12 h to remove N-methylpyrrolidone, thereby obtaining the polyolefin / graphene nanocomposite material.
7. A method for preparing a polyolefin / graphene nanocomposite material using mechanical shear force, characterized in that: It consists of the following steps: Graphene nanosheets, polypropylene powder and N-methylpyrrolidone were added into the torque rheometer; wherein the addition amount of graphene nanosheets was 2.5% of the total mass of graphene nanosheets and polypropylene powder, and the addition amount of N-methylpyrrolidone was 10% of the total mass of graphene nanosheets and polypropylene powder; The shear mixing was carried out at a temperature of 90° C. and a torque of 15 N·m for 30 minutes, 2 hours or 3 hours. The product after the shear mixing treatment was dried in a vacuum drying oven at 50° C. for 12 hours to remove N-methylpyrrolidone, thereby obtaining the polyolefin / graphene nanocomposite material.
8. The polyolefin / graphene nanocomposite material prepared by the method described in any one of claims 1 to 7.
9. The polyolefin / graphene nanocomposite material according to claim 8, characterized in that: The general formula of the polyolefin / graphene nanocomposite material is PP / Gx, where x represents the mass percentage of graphene nanosheets in the polyolefin / graphene nanocomposite material, and x is 1%-3.5%.
Citation Information
Patent Citations
Polymer-graphene nanocomposites
CN105452359A
Polymer / exfoliated NANO-composite films with superior mechanical properties
WO2020008372A1